Keeping up with the pace of digitization: The case of the Australian construction industry - Leviakangas, Pekka; Mok Paik, S.; Moon, S. (Elsevier BV, 2017)
Â© 2017 Elsevier Ltd The most significant current technological trend is digitization, the impacts of which will be faced by all levels of society. This paper addresses how the Australian construction industry has kept up with the pace of digitization compared with other industries in Australia. The data is drawn mainly from the national accounts hosted by the Australian Bureau of Statistics, within the time period of 1995â€“2015. Construction has developed into one of the most important industries in Australia. Together with mining and the financial and insurance sector, it has contributed to a significant gross added value (GVA) in the economy. The construction industry has invested around 1% or less in information and communication technologies (ICT) as their share of GVA; however, it has invested about 15% in ICT of their total investments (gross fixed capital formation). Among the selected industries, construction's labour productivity measured by GVA per hour was the third highest, despite low level of investments in digitization. The observed correlation between ICT investments and productivity is weak when using industry level data from the national accounts. Any big leap towards digitization is not recognised for the construction industry; rather there appears to be steady acceptance of the technology.